2015
DOI: 10.5812/jjm.28320
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Healing Effect of Alginate Sulfate Hydrogel Dressing Containing Antimicrobial Peptide on Wound Infection Caused by Methicillin-Resistant Staphylococcus aureus

Abstract: Background:Wound infections caused by methicillin-resistant Staphylococcus aureus are a health problem worldwide; therefore, it is necessary to develop new antimicrobial compounds. Considering broad-spectrum antimicrobial activity and low probability of drug resistance to peptides, applications these peptides are being studied extensively.Objectives:In this study, to control drug release over time, an alginate sulfate-based hydrogel impregnated with the CM11 peptide as the antimicrobial agent was developed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 29 publications
2
13
1
Order By: Relevance
“…Sulfated matrixes made from synthetic or naturally‐derived polymers have been recently used as a promising approach for stabilization and delivery of growth factors . Recently, it has been shown that the sulfation of ALG can facilitate its reversible electrostatic interaction with heparin‐binding proteins in a manner similar to heparin and heparan sulfate . In an interesting study, Cohen et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfated matrixes made from synthetic or naturally‐derived polymers have been recently used as a promising approach for stabilization and delivery of growth factors . Recently, it has been shown that the sulfation of ALG can facilitate its reversible electrostatic interaction with heparin‐binding proteins in a manner similar to heparin and heparan sulfate . In an interesting study, Cohen et al .…”
Section: Introductionmentioning
confidence: 99%
“…18 Recently, it has been shown that the sulfation of ALG can facilitate its reversible electrostatic interaction with heparin-binding proteins in a manner similar to heparin and heparan sulfate. [18][19][20][21][22][23] In an interesting study, Cohen et al showed that the sulfation of ALG improved its binding with ten known heparin-binding proteins. 24 They achieved the sustained release of basic fibroblast growth factors (bFGF) by mixing ALG and ALG-S, and showed that the release profile was a function of the percentage of bFGF bound to the hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…Alginate-based dressings were also evaluated in experimental models of wound infections using mice and rats [32,62]. For instance, the antimicrobial action of an alginate sulfate-hydrogel containing the synthetic peptide CM11 (WKLFKKILKVL-NH 2 ) was evaluated in a murine skin infection induced by a subcutaneous injection of methicillin-resistant S. aureus (MRSA) [32]. CM11 was chosen due to its potent antimicrobial action against several species including A. baumannii, Brucella melitensis, E. coli, S. aureus, and P. aeruginosa [76][77][78].…”
Section: Alginate-based Formulationsmentioning
confidence: 99%
“…Importantly, no existing product meets all the requirements of an ideal dressing. This scenario has encouraged the use of natural polymers, such as carbohydrates, in order to develop new formulations to be applied in the treatment of skin infections [23,[32][33][34][35][36]. In this descriptive review, we present the application of polysaccharide-based formulations in in vivo experimental models of skin wounds infections induced by bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Wound healing involves a series of complex and wellorchestrated events occurring after an injury or physical trauma to the skin, 12,13 that aims to completely restore the integrity of damaged tissue and reinstate it as a functional barrier. [14][15][16] However, in some extreme situations (i.e., trauma with large full-depth skin damage), 17 complete re-epithelialization takes a long time. 18 Therefore, extensive studies are focusing on wound dressing systems to promote better wound healing and to reduce scar formation.…”
Section: Introductionmentioning
confidence: 99%